Systematic Mispricing in European Equity Prices? - Marian Berneburg (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2007)
One empirical argument that has been around for some time and that clearly contra- dicts equity market efficiency is that market prices seem too volatile to be optimal estimates of the present value of future discounted cash flows. Based on this, it is deduced that systematic pricing errors occur in equity markets which hence can not be efficient in the Effcient Market Hypothesis sense. The paper tries to show that this so-called excess volatility is to a large extend the result of the underlying assumptions, which are being employed to estimate the present value of cash flows. Using monthly data for three investment style indices from an integrated European Equity market, all usual assumptions are dropped. This is achieved by employing the Gordon Growth Model and using an estimation process for the dividend growth rate that was suggested by Barsky and De Long. In extension to Barsky and De Long, the discount rate is not assumed at some arbitrary level, but it is estimated from the data. In this manner, the empirical results do not rely on the prerequisites of sta- tionary dividends, constant dividend growth rates as well as non-variable discount rates. It is shown that indeed volatility declines considerably, but is not eliminated. Furthermore, it can be seen that the resulting discount factors for the three in- vestment style indices can not be considered equal, which, on a risk-adjusted basis, indicates performance differences in the investment strategies and hence stands in contradiction to an efficient market. Finally, the estimated discount rates under- went a plausibility check, by comparing their general movement to a market based interest rate. Besides the most recent data, the estimated discount rates match the movements of market interest rates fairly well. – – Ein empirisches Argument besagt, dass Aktienpreise zu volatil sind, um optimale Schätzer des Barwerts zukünftiger Dividendenerträge zu sein. Auf Basis dieser Aussage wird gefolgert, dass systematische Schätzfehler an Aktienmärkten exitistieren, die eine Effizienz im Sinne der Hypothese Effizienter Märkte ausschließen. Das Paper versucht zu zeigen, dass diese so genannte "exzessive Volatilität" zu einem Großteil auf restriktive Annahmen zurückzuführen ist, die für die Schätzung des "korrekten" Barwerts der zukünftigen Erträge herangezogen werden. Basierend auf monatlichen Daten dreier Indizes, die verschiedene Investmentstrategien wiederspiegeln und einem integrierten europäischen Gesamtmarkt entstammen, wird auf alle üblichen Annahmen verzichtet. Dies wird mit Hilfe des Gordon Growth Models erreicht. Die Wachstumsraten der Dividenden werden mit einem Ansatz von Barsky und DeLong geschätzt. Als Erweiterung zu Barsky und DeLong werden allerdings die Diskontraten aus den bestehenden Daten approximiert. Es zeigt sich, dass in der Tat der Volatilitätsüberschuss der Marktpreise drastisch gesenkt wird. Allerdings verschwindet er nicht gänzlich, sondern bewegt sich grundsätzlich auf ähnlichem Niveau wie in einer früheren Studie des Autors, in der nur die Annahme, dass Dividenden einem stationären Prozess folgen, gelockert wurde. Ein weiteres Ergebnis des Paper ist, dass die geschätzen Diskontfaktoren der drei Investmentstrategien statistisch gesehen unterscheidlich sind, was für sich genommen darauf hindeutet, dass die Marktteilnehmer die risikoadjustierten Erträge dieser Strategien unterschiedlich einschätzen. Abschließend wurden die geschätzten Diskontraten einem Plausiblitätstest unterzogen. Es zeigte sich, dass abgesehen vom aktuellen Rand die geschätzten Diskontraten ein ähnliches Verhalten an den Tag legen wie ein marktbasierter Zinssatz.
urn:nbn:de:gbv:3:2-4897
Keywords: G12; G14; 330; equity market efficiency; discounted cashflow; excess volatility; variance bound test; rational expectations; Börsenkurs; Volatilität; Aktienmarkt; Effizienzmarktthese; Abzinsung; Cash Flow; Rationale Erwartung; Schätzung; Theorie; EU-Staaten